Podstawa traktatowa przyjmowania aktów prawa pochodnego z dziedziny środowiska i energii w prawie UE - Siwor, Przemysław (Studia Prawnoustrojowe, 2020)
Despite the considerable volume of the Court of Justice of the European Union (CJEU) case-law on Treaty basis for secondary legislation, the claim that any doubts concerning the choice of the Treaty basis for secondary legislation in the area of environment and energy in the EU law have been clarified is incorrect. On several occasions, the choice of the proper legal basis for such a legal act gave rise to serious doubts. It was unclear whether the subject matter of the act determined the application of Article 192(1) TFEU (ordinary legislative procedure) or Article 192(2), first paragraph of the TFEU (special legislative procedure). The aim of this article is to analyse the control criteria for the check of the Treaty basis for secondary legislation in the area of environment and energy conducted by the CJEU. This issue is considered in a broader context of the Treaty provisions, practice and the CJEU case law. The utmost attention is given to the judgement of the Court of Justice of the European Union issued on 21 June 2018 in the case C-5/16, Republic of Poland v European Parliament and Council of the European Union, where the Court dismissed the action for annulment of the Decision (EU) 2015/1814 of the European Parliament and of the Council of 6 October 2015 concerning the establishment and operation of a market stability reserve for the Union greenhouse gas emission trading scheme and amending Directive 2003/87/EC. The Author of the article comes to the conclusion that the Court, when reviewing the choice of the Treaty basis for a legal act, considers mainly its purpose and content, while the likely impact is of secondary importance. According to the Author, the judgement of the Court in the case C-5/16, Republic of Poland v European Parliament and Council of the European Union is likely to impede the application of Article 192(2)(c) TFEU (special legislative procedure) as a proper legal basis for legal acts in the area of environment which may affect a Member State’s energy mix.